UTILIZATION OF BETEL LEAVES EXTRACT TO PREVENT THE GROWTH OF Fusarium oxysporum f.sp. capsici 1 CAUSING FUSARIUM WILT DISEASE IN BELL PEPPER - Leana, Ni Wayan Anik; Suprapta, Dewa Ngurah (Universitas Lampung, 2021)
Utilization of betel leaves extract to prevent the growth of Fusarium oxysporum f.sp. capsici causing fusarium wilt diseasein bell pepper. Betel (Piper betle Linn.) is commonly used in Indonesian traditional medicine due to its antimicrobial properties,thus it is often used as an ingredient in natural pesticides. The effectiveness of betel leaf extract as a control for Fusariumoxysporum in several plants showed it’s potential to control the fungi in bell pepper. F. oxysporum f.sp. capsici is one of theimportant pathogens causing Fusarium wilt disease in bell pepper. It is one of the most devastating plant diseases due to itsability to cause a crop failure. The test on the inhibitory capacity of betel leaf extract on the growth of F. oxysporum f.sp.capsici were carried out by growing the fungi on PDA mixed with various concentrations of betel leaf extracts. The resultsshowed that betel leaf extract treatment at 0.02% concentration was able to inhibit the growth of F. oxysporum f.sp. capsici inPDA at 95.54%. The full inhibition of colony growth (100%) was achieved in the extract treated with the concentration of0.03%. Meanwhile treatment of 0.17% betel leaf extract was able to inhibit the growth of F. oxysporum f.sp. capsici on bellpepper stems. Following this result, fractionation of the betel leaf extract by column chromatography was conducted, resultingin 44 fractions. The bioassays of those fractions showed that, there were seven fractions that reveal inhibition capabilityagainst F. oxysporum f.sp. capsici.